COVD-04. REAL-WORLD PERSPECTIVES: TUMOR TREATING FIELDS (TTFIELDS) UTILITY TO OPTIMIZE TREATMENT OF PATIENTS WITH GLIOBLASTOMA (GBM) AMIDST COVID-19 PANDEMIC - Frongillo, Peggy (Neuro Oncol, 2020)
INTRODUCTION: Due to the unprecedented, COVID-19 pandemic and resulting health/safety guidelines, rapid-adjustments to treatment plans for patients battling glioblastoma (GBM; debilitating, aggressive cancer) were critical. Tumor Treating Fields (TTFields; FDA-approved for GBM; antimitotic device) are alternating electric fields (200 kHz) delivered through scalp-placed transducer arrays to target rapidly dividing GBM cells. Visitor restrictions at cancer-centers and often overburdened healthcare teams provided obstacles to cancer therapy. Health and safety of patients/caregivers, healthcare providers (HCPs), and patient Device Support Specialists (DSS) were prioritized. We evaluated the impact of Novocure® (device manufacturer) implemented strategies on overcoming limitations/restrictions to treatment-access during COVID-19. TREATMENT/PROTOCOL: TTFields (Optune) offers a viable noninvasive, built-in-care system for convenient at-home use. TTFields provides survival benefit with continuous, portable-usage and is tolerable (no-related systemic effects) without overall impact on quality-of-life (except itchy skin). Novocure adopted/amended protocols to meet health guidance/regulation (ie, World Health Organization, Centers for Disease Control and Prevention, local, hospital/clinic directives). PERSPECTIVES: COVID-19 forced a change in treatment patterns imposed by quarantine limitations. This, coupled with the vulnerabilities of immunocompromised patients with GBM, necessitated new-access to TTFields. A COVID-19 task force was created to monitor developments, providing directives to minimize risks to patients/caregivers and employees. Hygiene-practices/full-personal protective equipment were applied for live patient-appointments with DSS. Virtual education appointments were executed to guide patients/caregivers through treatment-initiation. New, no-contact, monthly-usage data downloads were employed. Communication measures were implemented, informing HCPs of process changes impacting patients. To date, no observed differences were noted for virtual to non-virtual patient starts, demographics, time-to-start (42-days), treatment discontinuations, percentage continuing therapy (90%), and overall complaints. No new safety signals were observed utilizing new approaches. CONCLUSIONS: TTFields care-delivery has been transformed during COVID-19 and preemptively in regards to other future access-limiting events, with adoption of virtual-platforms/protocols, resulting in enhanced access and education for patients/caregivers and healthcare teams.